Leadership, Collaboration, and Satisfaction: A Structural Model of Teachers’ Normative Commitment in Islamic Elementary Schools - Afifah Nurul Khoirot Nasution; Candra Wijaya; Muhammad Dalimunthe (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study investigates the direct and indirect effects of the head of madrasah’s charismatic leadership and teamwork on teachers’ normative commitment, with job satisfaction serving as a mediating variable. Methodology: Employing a quantitative approach with a survey design, data were collected from 101 teachers of State Islamic Elementary Schools (MIN) in Asahan Regency using proportional random sampling. Path analysis was applied to examine the causal relationships among variables. Main Findings: findings reveal that charismatic leadership and teamwork significantly influence teachers’ job satisfaction. Furthermore, both variables have direct positive effects on teachers’ normative commitment. Job satisfaction demonstrates the strongest direct effect on normative commitment and significantly mediates the influence of charismatic leadership and teamwork. These results indicate that teachers’ moral obligation and loyalty to their institutions are shaped not only by leadership quality and collaborative work culture but also by their level of satisfaction with work conditions and professional recognition. Novelty/Originality of this study: The study contributes to educational management literature by emphasizing normative commitment as a critical yet underexplored dimension of teacher commitment in madrasah contexts. Practically, the findings suggest that strengthening charismatic leadership practices, fostering effective teamwork, and improving job satisfaction are strategic pathways to enhancing teachers’ commitment and sustaining educational quality in Islamic elementary schools.